Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0101915
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Surgical Safety Checklist in Switzerland and Perceptions of Its Benefits: Cross-Sectional Survey

Abstract: ObjectivesTo examine the implementation of the Surgical Safety Checklist (SSC) among surgeons and anaesthetists working in Swiss hospitals and clinics and their perceptions of the SSC.MethodsCross-sectional survey at the 97th Annual Meeting of the Swiss Society of Surgery, Switzerland, 2010. Opinions of the SSC were assessed with a 6-item questionnaire.Results152 respondents answered the questionnaire (participation rate 35.1%). 64.7% respondents acknowledged having a checklist in their hospital or their clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 45 publications
4
36
1
2
Order By: Relevance
“…Levy and colleagues 30 noted that despite 100% documentation of SSC completion, not all components of the SSC were completed as defined. 30 Cullati and colleagues 24 found similar results in university hospitals in Switzerland. The "briefing" and "time out" were completed 90% and 83% of the time, respectively; however the "debriefing" was completed only 47% of the time.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Levy and colleagues 30 noted that despite 100% documentation of SSC completion, not all components of the SSC were completed as defined. 30 Cullati and colleagues 24 found similar results in university hospitals in Switzerland. The "briefing" and "time out" were completed 90% and 83% of the time, respectively; however the "debriefing" was completed only 47% of the time.…”
Section: Discussionmentioning
confidence: 62%
“…This opinion echoes the sentiment noted in another study in which participants strongly disagreed with the statement "[the SCC] brings no added value to existing safety procedures." 24 The ability of the SSC to have bene fits beyond improved morbidity and mortality has been established within the literature. Health care providers included in the qualitative study by Thomassen and colleagues 25 evaluating nurses' and physicians' acceptance of the SSC felt that it was able to reveal insufficient equipment standardization and improve physiciannurse cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…4). 9,[32][33][34][35][36]40,42,43 Improvements noted were increased ''team feeling,'' 36 ''strengthened teamwork and efficiency,'' 33 and identified enhanced team communication evidenced by increased discussion of critical events. 40 Studies undertaken 1-year postimplementation reported 47 to 57% of medical personnel found SSC improved communication.…”
Section: Staff Perceptionmentioning
confidence: 99%
“…6). 9,32,34,36,37,39,43 While studies noted differing, yet positive responses about the ability of the SSC to prevent errors, all studies reported only minor improvement in team awareness. Specifically, team members reported that the SSC provided brief pertinent information about patient's history and risk, as well as the required procedure, increasing overall situational awareness.…”
Section: Staff Perceptionmentioning
confidence: 99%
See 1 more Smart Citation